Implementasi Pengelolaan Sumber Daya Laut Nasional Terhadap Kebijakan Pemerintah Provinsi Kepulauan Riau - Mirza, Ahmad Chaidir; Anggraini, R.A. Rini; Soetijono, Iwan Rachmad (Lentera Hukum, 2017)
Riau Islands Province is an island-based region consisting of a group of islands. The Province has a very strategic geographic location due to bordering the neighboring countries in Southeast Asia, viz. Singapore, Brunei Darussalam, Malaysia, Cambodia, and Vietnam. It is different from other Island-based provinces, in which it lies in the hub areas of Malacca Strait. It shows that the Province is an important location to trade from America, Europe and Asia, in addition to a plenty of marine resources that will potentially maximize local government’s revenue and prosper society in the province. However, such marine resource has not been well-managed by local government by which in 2013 the figure shows poverty rate remains high. The decline of poverty rate counts only in urban areas where they do not lie in submarine areas, but the poverty has increased and could not be well-resolved. It asserts that the Government of Riau Islands has not maximized local powers to resolve poverty problems in the region. Keywords: Policy, Local Government, National Marine Resources